The Dynamics of Sasi in Kaimana: the Institutional Change over Traditional Marine Resource Management - Patriana, Ratna; Adiwibowo, Soeryo; A. Kinseng, Rilus; Satria, Arif (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTSasi, as a regime of common (pool) resource management, has long been trusted as one of the most efficient traditional practices in maintaining the sustainability of resources in coastal areas. However, the practice of Sasiwas highly influenced by adat, customary laws set by feudal system that have been replaced by the modern state. This research intended toexamine (1) how the practice of Sasi has changed along with the ecological, social, and economic changes that happened within the society, and (2) what was the impact of this change to the mechanism of the distribution of wealth within the localcommunity. Field research was conducted inthe Kaimana District, West Papua Province,from November - December 2015, using qualitative methods and progressive contextualization strategy.The results indicated that the economic changes were the main driving factor of the dynamic of Sasi in Kaimana. The commercialization of Sasi by village elites hasreplaced this tradition of marine conservation and its orientation with the mechanism ofsurplus accummulation. It degraded the social security mechanism, affectedthe income of the community in general,and developed intimate exclusionsof the sub-ordinate groups,includingwomen.Keywords: coastal resource, social change, social security, intimate exclusion.ABSTRAKSasi, sebagai suatu rezim pengelolaan sumberdaya alam milik bersama, telah lama dipercaya sebagai salah satu praktek tradisional yang efisien dalam memelihara kelestarian sumberdaya di wilayah laut. Namun demikian, praktek Sasi ini sangat dipengaruhi oleh adat yang didirikan oleh sistem feodal, suatu sistem yang kini telah digantikan oleh pemerintahan modern. Penelitian ini bertujuan untuk menjelaskan (1) bagaimana praktek Sasi telah berubah sejalan dengan perubahan ekologi, sosial dan ekonomi yang terjadi di masyarakat, dan (2) bagaimana dampak perubahan tersebut terhadap mekanisme distribusi kemakmuran di dalam komunitas. Studi lapangan dilakukan pada November – Desember 2016 di Kabupaten Kaimana, Papua Barat, dengan menggunakan metode kualitatif dan strategi penelitian progressive contextualization. Hasil penelitian menunjukkan bahwa perubahan ekonomi adalah yang paling berpengaruh terhadap dinamika Sasi di Kaimana. Komersialisasi Sasi oleh elit desa telah menggeser tradisi konservasi laut serta orientasinya dengan mekanisme akumulasi surplus bagi rumah tangga. Hal ini menyebabkan tergedradasinya mekanisme jaminan sosial masyarakat secara umum, dan menimbulkan intimate exclusion terhadap kelompok sub-ordinat, termasuk perempuan.Kata kunci: sumberdaya laut, perubahan sosial, jaminan sosial, eksklusi karib.